Mammalian fossils from Gruta do Ioiô cave and past of the Chapada Diamantina, northeastern Brazil, using taphonomy, radiocarbon dating and paleoecology. (March 2020) - Eltink, Estevan; Castro, Mariela; Montefeltro, Felipe Chinaglia; Dantas, Mario André Trindade; Scherer, Carolina Saldanha; de Oliveira, Paulo Victor; Langer, Max Cardoso
Abstract: Gruta do Ioiô is a cave part of Iraquara carstic system (Salitre Formation, Una Group). Located in the region of the Chapada Diamantina, northeastern Brazil, this partially submerged cave has yielded abundant fossil remains that until now included Siluriformes, an alligatorid crocodilian and a set of mammals, such as representatives of Mustelidae, Rodentia and Chiroptera. Besides the record of Palaeolama major (Camelidae), Pecari tajacu (Tayassuidae), both yielded from subaquatic site, Puma concolor, Leopardus pardalis (Felidae), Chrysocyon brachyurus (Canidae), and a Didelphidae indet. were yielded from newly described subaerial site. Taphonomic features, such as weathering, transport, breakage, bones and taxonomic representation, demonstrate that bioestrationomic and fossildiagenetic conditions varies between fossiliferous accumulations in the cave, and differences are still observed in the same fossil-bearing site (subaerial). The radiocarbon ages indicate the occurrence of Leopardus pardalis at 30, 351–30, 862 yr cal BP, Palaeolama major at 24, 854–25, 379 yr cal BP and Pecari tajacu at 8170–8336 yr cal BP. It extends the time range of Gruta do Ioiô fossils from the Late Pleistocene to the Early-Middle Holocene, encompassing the Last Glacial Maximum. Paleoecological inferences provided by stable isotopes (δ 13 C) suggest great proportion of diets based on C3 plants along the trophic levels, suggesting a denser forest environment and more humid conditions in the region of Gruta do Ioiô cave during the Quaternary. The record of taxa, such as Myocastor coypus (a semiaquatic rodent currently distributed in subtropical and temperate South America) and Chrysocyon brachyurus (a typical dweller of open grasslands) shows that past landscape, composed by forests and/or savannic vegetations, contrasts with xeric arboreal scrubland that currently covers the area. Highlights: A carstic cave provides a time range from the Late Pleistocene to the Early-Middle Holocene for fossiliferous accumulation. The description of fossils from different accumulations in the cave reveals distinguished taphonomic conditions. Isotopes indicate the presence of forests in the past, contrasting with xeric scrubland that currently covers the area.